Protein Rekombinan Outer Membrane Protein-31 dengan Superoxide Dismutase pada Pichia Pastoris Berpotensi Sebagai Kandidat Vaksin Brucellosis - Kusumawati, Arizah; Wijaya, Sri Kartika; Husnaa, Ulfatul; Rubiyana, Yana; Santoso, Adi (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Brucellosis is zoonotic disease caused by Brucella infections transmitted to human either direct contact with animals or consume their products. This becomes problematic in the world especially in endemic countries of Brucella and development countries. Brucella melitensis is one of pathogenic species from genus Brucella. Combining immunogenic side both the outer membrane protein 31 (OMP31) derived from B. melitensis and superoxide dismutase (SOD) derived from B. abortus has the potential to be developed as a candidate for recombinant vaccine. In this study, the expression protein of fusion OMP31-SOD inserted in pPIC9K plasmid with extra His-tag sequence, intends to be developed as a recombinant protein vaccine. Recombinant plasmids pPIC9K+OMP31-SOD were transformed into Pichia pastoris KM71 using electroporation method. Selection of transformants was as performed using geneticin® concentrations of 0.25 mg/mL – 4 mg/L Selected transformants were grown to express the OMP31-SOD recombinant protein. Protein expression was confirmed using both of dot-blot method and electrophoresis with Coomassie Brilliant Blue (CBB) staining. The OMP31-SOD recombinant protein was successfully expressed extracellular by Pichia pastoris KM71 clones 3, 4, and 6 with a molecular weight approximately 40 KDa.